Epigenetic Effects of Addictive Drugs in the Nucleus Accumbens - Anderson, Ethan M.; Taniguchi, Makoto (Frontiers in Molecular Neuroscience, 2022)
Substance use induces long-lasting behavioral changes and drug craving. Increasing evidence suggests that epigenetic gene regulation contributes to the development and expression of these long-lasting behavioral alterations. Here we systematically review extensive evidence from rodent models of drug-induced changes in epigenetic regulation and epigenetic regulator proteins. We focus on histone acetylation and histone methylation in a brain region important for drug-related behaviors: the nucleus accumbens. We also discuss how experimentally altering these epigenetic regulators via systemically administered compounds or nucleus accumbens-specific manipulations demonstrate the importance of these proteins in the behavioral effects of drugs and suggest potential therapeutic value to treat people with substance use disorder. Finally, we discuss limitations and future directions for the field of epigenetic studies in the behavioral effects of addictive drugs and suggest how to use these insights to develop efficacious treatments.